Status of urban social development of Eastern Uttar Pradesh: A geographical analysis - Ankit Kumar Gupta,; Kapil Kumar Gavsker, (National Geographical Journal of India, 2024)
Regions undergo a significant developmental process. The early developments are characterized by economic growth and its expansion, while the latter the social well-being becomes paramount. The measurement of social well-being of urban population is equally important when society is undergoing transformation. This study aims to find out social well-being in terms of demographic characteristics of the eastern region of Uttar Pradesh. According to 2011 census, Uttar Pradesh has registered lower rate of urbanization in comparison to national average. Among the four regions of Uttar Pradesh, Eastern Uttar Pradesh is least urbanized region of the state. This reflects important regional disparities. It is important to assess social well-being status of urban population of the region. This study is based on secondary source of data retrieved from Census. Pearson Correlation Coefficient is also calculated to examine relation between various indicators. The result of study shows that the level of social well-being is comparatively higher in those districts where the major urban agglomerations are located and they are also economically viable areas.